Error Analysis on Essay Writing Organization - apandi, apandi; kusriandi, wendi (Academic Journal PERSPECTIVE: Education, Language, and Literature, 2016)
This  research  is  designed  to  analyze  students’  error  on  essay  writing organization.  The  writers  focus  on  the  one  category  of  error  identifications  that  is organization.  By  conducting  this  research,  the  writers  hope  some  development  of students’ ability in arranging essay.  By  analazing  the  erros,  students  get  feed  back  to develop their ability. This study was conducted descriptively and qualitatively in nature. It is designed to identify and to describe kinds of errors is made by the student in essay writing organization in the EFL classroom. To achieve the goal, the writers describe in detail all the data taken from the students’ works and interpreted to make an empirical generalization. This  research  was conducted  in  second  grade  of English  department  in one of the university in Cirebon. The writers use purposive random sampling. The result of  findings  show  that  16  students  stand  in  scale  3  which  is  equal  with  64  %.  Then,  7 students  stand  in  scale  4  which  is  equal  with  28  %.  And  the  last,  2  students  stand  in scale  2  which  is  equal  with  8  %.  So  that,  the  writer  concluded  that  the  students  of second  grade  of  UNSWAGATI  Cirebon  are  adequate  to  fair  on  essay  writing organization.